Repair bond strength of resin composite to CAD/CAM glass-ceramic: Influence of cleaning methods, surface treatments, and aging - Bessa, Mariana Silva de; Marinho, Liliane Cristina Nogueira; Miranda, Larissa Mendonça de; Carvalho, Isabelle Helena Gurgel de; Campos, Bruna Oliveira [UNESP]; Borges, Boniek Castillo Dutra; Calderon, Patrícia dos Santos; Souza, Rodrigo Othávio de Assunção e (Elsevier, 2025)
Objective: To evaluate the influence of different cleaning methods, surface treatments, and aging on the repair bond strength to a CAD/CAM glass-ceramic. Materials and methods: Forty-eight lithium disilicate CAD/CAM ceramic blocks were fabricated, sintered, and embedded in acrylic resin. After contamination with human saliva, they were divided according to the factors “Cleaning method” (Control-water/air spray, Air-particle abrasion with Al2O3, Ivoclean cleaning paste), “Surface treatment” (5 % Hydrofluoric acid-HF + Silane, Monobond Etch & Prime-MEP), and “Aging” (thermocycling, no thermocycling). Cylinders of resin composite were built, and Shear Bond Strength (SBS) was tested. Data were analyzed with 3-way ANOVA, Tukey's post-test, and Weibull modulus and failure analyses and Scanning Electron Microscopy of the surfaces were performed. Results: Significant factors affecting SBS were cleaning method and aging. Surface treatment had an influence but was not statistically significant (p = 0.0591). The IMEP (11.10±2.90A), APHF (9.78±2.13AB) and IHF (9.61±2.20AB) groups presented the highest SBS values, which were statistically superior to the IMEPTC (5.36±1.17F), IHFTC (5.52±1.71EF), APHFTC (5.80±1.20DEF), HFTC (5.82±1.33DEF), MEPTC (5.92±1.82DEF) and HF (6.62±1.77CDEF) groups. Weibull analysis showed no significance (p = 0.096), but characteristic strength was. Failure analysis revealed a predominance of mixed type 1 failure (adhesive and cohesive resin). Conclusion: Air-particle abrasion with Al2O3 and Ivoclean improved SBS compared to the control group and MEP showed similar results to HF + Silane, making it a viable alternative for glass-ceramic repair. Moreover, thermocycling reduced the bond strength compared to the groups without aging, with the effect being more pronounced in the groups treated with HF followed by silane. Clinical Significance: Lithium disilicate ceramic repair with resin composite is more effective when the ceramic is first decontaminated using a cleaning agent or air-particle abrasion. For conditioning, either MEP or HF followed by silane can be used; however, MEP presents lower toxicity.
Keywords: Dental prosthesis repair; Lithium disilicate; Resin composite; Shear Strength